Pengaruh Pengetahuan Kewirausahaan, Motivasi Berwirausaha, dan Kreativitas terhadap Minat Berwirausaha Mahasiswa Universitas Muhammadiyah Jember (Jurnal Simki Economic, 2025)
Student interest in entrepreneurship is very important to produce a creative and independent young generation. However, the level of interest is still relatively low, which is often caused by lack of funds, fear of failure, and the time needed to launch and operate a company is very short. The purpose of this study was to investigate how students' interest in entrepreneurship at the University of Muhammadiyah Jember is influenced by their entrepreneurial knowledge, motivation, and creativity. By distributing questionnaires, this study used survey techniques and quantitative approaches. Purposive sampling procedures and proportional stratified random sampling were used to select 200 respondents as samples from a total population of 8,362 students. Multiple linear regression was used to examine the data after the classical assumptions were tested. According to the results of the study, students' interest in entrepreneurship at the University of Muhammadiyah Jember is positively and significantly influenced by three independent variables, namely entrepreneurial knowledge, entrepreneurial motivation, and creativity.